Analisis Persediaan Kedelai Sebagai Bahan Baku Pembuatan Tahu Pada Industri Tahu Mekar di Kelurahan Liabuku Kecamatan Bungi Kota Bau-Bau - Minartin, Minartin; Rianse, Usman; Taridala, Sitti Aida Adha (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2018)
This study aimed to determine: (1) identify soybean raw material inventory, (2) calculate the inventory of raw materials before and after using the EOQ analysis, and (3) analyze the time of re-ordering the raw materials to avoid running out of stock the soybean in warehouse storage. Â This research is a case study so that manager of Tahu Mekar Industry as a source for obtaining information in accordance with the needs of researchers. Data were analyzed using descriptive analysis and EOQ, TIC, Safety Stock and ROP analytical. Research results are as follows: First, the type of soybean used are soybean imports from Surabaya City and local soybean from Ereke, North Buton. The volume of imported soybean purchases as much as 10,000 kg and 1,000 kg with the local price of Rp 8,000 per kg. Second, total supply of raw material to the Tahu Mekar Industry is not optimal with a difference of as much as 6,424.16 kg and difference in total cost of raw material inventory of Rp 85,239.51. Third, in order not to run out of stock of raw materials, the storage warehouse safety stock should always be available in warehouse storage of as much as 2,333 kg and perform reordering of raw materials during storage warehouse inventory of raw materials as much as 3,833 kg.